# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime } = \frac {1}{x^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1}{\sqrt {x +2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \sqrt {x^{2}+9}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {10}{x^{2}+1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \cos \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1}{\sqrt {-x^{2}+1}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \,{\mathrm e}^{-x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -y-\sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x +y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y-\sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x -y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y-x +1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x -y+1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2}-y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2}-y-2
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 x^{2} y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \ln \left (y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{{1}/{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{{1}/{3}}
\] |
✓ |
✓ |
|
\[
{}y y^{\prime } = x -1
\] |
✓ |
✓ |
|
\[
{}y y^{\prime } = x -1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \ln \left (1+y^{2}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2}-y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 x y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 x y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right ) y^{\prime } = 4 y
\] |
✓ |
✓ |
|
\[
{}2 \sqrt {x}\, y^{\prime } = \sqrt {1-y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 \sqrt {x y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 4 \left (x y\right )^{{1}/{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 x \sec \left (y\right )
\] |
✓ |
✓ |
|
\[
{}\left (-x^{2}+1\right ) y^{\prime } = 2 y
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime } = \left (1+y\right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x y^{3}
\] |
✓ |
✓ |
|
\[
{}y y^{\prime } = x \left (1+y^{2}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1+\sqrt {x}}{1+\sqrt {y}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\left (x -1\right ) y^{5}}{x^{2} \left (2 y^{3}-y\right )}
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) \tan \left (y\right ) y^{\prime } = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1+x +y+x y
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } = 1-x^{2}+y^{2}-x^{2} y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y \,{\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 x^{2} \left (1+y^{2}\right )
\] |
✓ |
✓ |
|
\[
{}2 y y^{\prime } = \frac {x}{\sqrt {x^{2}-16}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 4 x^{3} y-y
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+1 = 2 y
\] |
✓ |
✓ |
|
\[
{}\tan \left (x \right ) y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y = 2 x^{2} y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 x y^{2}+3 x^{2} y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 6 \,{\mathrm e}^{2 x -y}
\] |
✓ |
✓ |
|
\[
{}2 \sqrt {x}\, y^{\prime } = \cos \left (y\right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = 2
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 y = 3 \,{\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+3 y = 2 x \,{\mathrm e}^{-3 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 x y = {\mathrm e}^{x^{2}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+2 y = 3 x
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime }+y = 10 \sqrt {x}
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime }+y = 10 \sqrt {x}
\] |
✓ |
✓ |
|
\[
{}y+3 x y^{\prime } = 12 x
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y = x
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime }-3 y = 9 x^{3}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = 3 x y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+3 y = 2 x^{5}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-3 y = x^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 x y = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (1-y\right ) \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right ) y^{\prime }+y = \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = 2 y+x^{3} \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y \cot \left (x \right )+y^{\prime } = \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1+x +y+x y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = 3 y+x^{4} \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 x y+3 x^{2} {\mathrm e}^{x^{2}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+\left (2 x -3\right ) y = 4 x^{4}
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+4\right ) y^{\prime }+3 x y = x
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime }+3 x^{3} y = 6 x \,{\mathrm e}^{-\frac {3 x^{2}}{2}}
\] |
✓ |
✓ |
|
\[
{}\left (x +y\right ) y^{\prime } = x -y
\] |
✓ |
✓ |
|
\[
{}2 x y y^{\prime } = x^{2}+y^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y+2 \sqrt {x y}
\] |
✓ |
✓ |
|
\[
{}\left (x -y\right ) y^{\prime } = x +y
\] |
✓ |
✓ |
|
\[
{}x \left (x +y\right ) y^{\prime } = y \left (x -y\right )
\] |
✓ |
✓ |
|
\[
{}\left (x +2 y\right ) y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}y^{2} y^{\prime } x = y^{3}+x^{3}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } = x y+x^{2} {\mathrm e}^{\frac {y}{x}}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } = x y+y^{2}
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime } = x^{2}+3 y^{2}
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-y^{2}\right ) y^{\prime } = 2 x y
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime } = y^{2}+x \sqrt {4 x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y+\sqrt {x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}y y^{\prime }+x = \sqrt {x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}x \left (x +y\right ) y^{\prime }+y \left (3 x +y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {x +y+1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (y+4 x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}\left (x +y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+2 x y = 5 y^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } y^{2}+2 x y^{3} = 6 x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y+y^{3}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+2 x y = 5 y^{4}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+6 y = 3 x y^{{4}/{3}}
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime }+y^{3} {\mathrm e}^{-2 x} = 2 x y
\] |
✓ |
✓ |
|
\[
{}y^{2} \left (x y^{\prime }+y\right ) \sqrt {x^{4}+1} = x
\] |
✓ |
✓ |
|